Hubungan Pengetahuan dan Sikap Ibu Nifas dalam Melakukan Perawatan Luka Pereneum di Praktek Mandiri Bidan Leli Kecamatan Datuk Tanah Datar Kabupaten Batu Bara Tahun 2022 - Susilawati Susilawati; Deby Cyntia Yun; Lasria Simamora; Retno Wahyuni (Jurnal Anestesi, 2024)
BACKGROUND Postpartum infections still play a role as the main cause of maternal death, especially in developing countries like Indonesia. This problem occurs as a result of midwifery services which are still far from perfect. Other factors causing postpartum infections include poor immune system, poor postpartum care, malnutrition/ malnutrition, anemia, poor hygiene, and fatigue. As a result of improper care of the perineum, it can result in the condition of the perineum being affected by locchea and moisture which will really support the growth of bacteria which can cause infections in the perineum. Infection not only hinders the wound healing process but can also cause damage to the supporting cell tissue, thereby increasing the size of the wound itself, both in length and depth. The causes of maternal death in Indonesia are still dominated by bleeding (32%) and hypertension in pregnancy (20%), followed by infection (5%), prolonged labor (10%), and abortion (5%) apart from obstetric causes, maternal death is also caused by other causes (non-obstetric) amounting to 35% (Indonesian Health Profile, 2019).OBJECTIVE: Knowing the relationship between knowledge and attitudes of postpartum mothers in caring for perenium wounds in the independent practice of Leli midwives, Datuk Tanah Datar sub-district, Batu Bara Regency in 2022. METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted, the statistical test results show a significant relationship. RESULTS: knowledge of postpartum mothers and attitudes of postpartum mothers in caring for perennial wounds in the independent practice of Leli midwives, Datuk Tanah Datar subdistrict, Batubara district in 2022. Suggestions are given for research and for research sites and for educational institutions regarding perennial wound care. Suggestions are given for research and for research sites and for educational institutions regarding Bounding Attachment.